Cambodian STEM pre-service teachers’ competency in effective information communication technology integration teaching based on technological pedagogical content knowledge framework - Im, Rany; Thy, Savrin; Iwayama, Tsutomu; Osa, Masashi (Journal of Science and Education (JSE), 2024)
This study explores how Cambodian STEM (Science, Technology, Engineering, and Mathematics) pre-service teachers comprehended the Technological Pedagogical Content Knowledge (TPACK) and its components, content knowledge (CK), pedagogical knowledge (PK), technological knowledge (TK), pedagogical content knowledge (PCK), technological pedagogical knowledge (TPK), technological content knowledge (TCK) and their associations with demographic variables. Using a self-report questionnaire, the study surveyed 440 pre-service teachers from three distinct teacher training colleges. Data was analyzed using descriptive statistics, independent t-test, and Pearson's correlation. Results showed that pre-service teachers rated themselves above the mean in all components: TPK and CK were the highest, and TCK and TPACK were the lowest. There was a significant difference in the gender and foreign language variables; males and being able to understand foreign languages were the favor. A negative relationship existed in age variables where younger pre-service teachers demonstrated higher competence in all aspects of TPACK except PCK. It concluded that Cambodian STEM pre-service teachers demonstrate adequate knowledge of content, pedagogy, and technology to integrate information communication and technology (ICT) into their teaching. Possessing a medium to a high level of TPACK, additional professional development programs are needed to assist pre-service teachers in reaching the highest TPACK level.